Pengaruh Ukuran Perusahaan, Debt To Equity Ratio, Current Ratio, Dan Return On Asset Terhadap Nilai Perusahaan Pada Perusahaan Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2020 - Yuliana Yuliana; Jocelyn Jocelyn; Alex Kurniawan (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to analyze the variables mentioned above in relation to the market capitalization of food and beverage companies listed on the Indonesia Stock Exchange between 2017 and 2020. The research strategy used is quantitative. This study uses a purposeful selection strategy to select 12 banking institutions that have been listed on the Indonesia Stock Exchange within four years before the research began. Researchers observe that company size, debt to equity ratio, current ratio, and return on assets all have a significant simultaneous effect on food and beverage companies listed on the Indonesia Stock Exchange between 2017 and 2020 scores. Companies involved in the food and beverage industry are listed on the Indonesia Stock Exchange will have a value that fluctuates in part depending on its size between 2017 and 2020. Between 2017 and 2020, the stock prices of food and beverage companies listed on the Indonesia Stock Exchange Exchange have a sizeable correlation with their debt-to-equity ratio . No statistically significant effect of the current ratio in the market can be seen for 2017-2020. companies involved in the production and distribution of food and beverages in Indonesia, as measured by their market value on the Indonesia Stock Exchange. Food and beverage companies traded on the Indonesia Stock Exchange saw less impact on their return on assets on their share prices between 2017 and 2020. Keywords: Company Size, Debt To Equity Ratio, Current Ratio, Return On Assets, Company Value